2020
DOI: 10.34172/ijtmgh.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Destination Choice in Medical Tourism

Abstract: Introduction: Although many factors can affect the choice of destination in medical tourism, some factors are indispensable to medical tourists and medical tourism. The aim of this study was to analyze important factors affecting the selection of a destination by potential medical tourists. Methods: This descriptive, cross-sectional study, conducted in Turkey, included a population of 1700 people and a sample size of 317 people selected through purposive sampling. Values were evaluated with a 95% confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…The findings showed that only accessibility and 'self-congruity' are positively associated with behavioural intentions (Hashemi et al, 2020). These results were also confirmed by Haneef (2017), Lee and Lee (2017), while Çapar and Aslan (2020) found that accessibility is significantly linked to tourists' behaviour.…”
Section: Accessibilitysupporting
confidence: 72%
“…The findings showed that only accessibility and 'self-congruity' are positively associated with behavioural intentions (Hashemi et al, 2020). These results were also confirmed by Haneef (2017), Lee and Lee (2017), while Çapar and Aslan (2020) found that accessibility is significantly linked to tourists' behaviour.…”
Section: Accessibilitysupporting
confidence: 72%
“…The involvement of tourists has been considered a prominent concept that plays an important role in the relationship of destination brand association and the revisit intention of medical tourists to understand leisure, recreation and health tourism behaviours (Gross and Brown, 2006; Hu and Yu, 2007; Lee et al , 2008). Thus, the current research attempts on destination brand equity in tourism destinations and tourist's revisit intention with regard to healthcare tourism destination, which is yet to be reported to contribute further in medical tourism literature (Chomvilailuk and Srisomyong, 2015; Das and Mukherjee, 2016; Kim and Lee, 2018; Polas et al , 2019; Çapar and Aslan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Medical services companies operate in a dynamic and competitive environment and the quality of service is becoming a strong strategic advantage in winning customers. Nevertheless, the fact that many countries with poor health systems invest in this area is evidence that medical tourism is seen as a very important business opportunity [16].…”
Section: Discussionmentioning
confidence: 99%